Reliability, Validity, and Interpretation of the Dependence Scale in Mild to Moderately Severe Alzheimer's Disease. (December 2013) - Lenderking, William R.; Wyrwich, Kathleen W.; Stolar, Marilyn; Howard, Kellee A.; Leibman, Chris; Buchanan, Jacqui; Lacey, Loretto; Kopp, Zoe; Stern, Yaakov
Introduction: The Dependence Scale (DS) was designed to measure dependence on others among patients with Alzheimer's disease (AD). The objectives of this research were primarily to strengthen the psychometric evidence for the use of the DS in AD studies. Methods: Patients with mild to moderately severe AD were examined in 3 study databases. Within each data set, internal consistency, validity, and responsiveness were examined, and structural equation models were fit. Results: The DS has strong psychometric properties. The DS scores differed significantly across known groups and demonstrated moderate to strong correlations with measures hypothesized to be related to dependence (| r | ≥ .31). Structural equation modeling supported the validity of the DS concept. An anchor-based DS responder definition to interpret a treatment benefit over time was identified. Discussion: The DS is a reliable, valid, and interpretable measure of dependence associated with AD and is shown to be related to—but provides information distinct from—cognition, functioning, and behavior.